PEMUNCULAN TINGKAT KESULITAN SOAL PADA TES PENJURUSAN MENGGUNAKAN REVISED BLOOM TAXONOMI (RBT) DI SMAN 1 BANGOREJO DENGAN APLIKASI WINGEN3 - Minarto Minarto (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
Before using Bloom's taxonomy theory which has been revised each held a study in class X still use Junior high school class IX and the value of UN and poll only, here there are many problems one of them is many students with a high value group IPS but are interested to enter the science department, many also vice versa children with high value IPA group results but in the poll select incoming IPS. In this research grouping difficulty level using the use of the Euclidian distance formula, the main important thing in grouping this problem is to determine the cluster center of the three groups of questions, which is a group of easy questions, groups of medium and groups of difficult problems. To determine the center of the cluster using the theory used by Suharsimi Arikunto (2005), from the theory is used to menententukan the cluster center, if the level of difficulty is between 0.71-1.00 then the problem can be said to be easy, and the range 0.71-1.00 can be called also with a cluster range is easy, while the classic center is 0.86, if the level of difficulty is between 0.31-0.70 then including the problem is , and the range 0.31-0.70 can be called as well as the medium cluster range, while its classic center is 0.50, and if the difficulty level is between 0.00-0.30 then the problem can be said to be difficult, and the range 0.00-0.30 can be called also with the cluster range is difficult, while the classic center is 0.15. Wingen3 is later used to direct prospective students to a selection of questions that are appropriate to the student's own abilities and interests. In the problem if tested with the value of the parameter μ = 3 and σ = 1, then the tendency of the problem is easy, while if the value of μ = 5 and σ = 1, the tendency to arise is about being and for the value of μ = 7 and σ = 1, the tendency of problems that arise is difficult.